2017
DOI: 10.1007/s10997-017-9381-9
|View full text |Cite
|
Sign up to set email alerts
|

Governance and performance of MFIs: the Cameroon case

Abstract: The main challenge of microfinance institutions and social economy firms remains their survival, and to meet this challenge, MFIs need to be competitive. The poor performance of MFIs is usually attributed to their decision-making and operational processes. The governance of MFIs is therefore identified as one of their main risks. Despite this, governance is still little explored in these organizations and empirical studies find a weak relationship between classical governance mechanisms and MFI performance, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Morais et al (2017) show that women are the driving force in SEOs like SECs. By contrast, Wamba et al (2018) show that the presence of women has a negative effect on the social and financial performance of these organizations. This fuzziness is troubling, considered that gender equality is endemic to the very concept of SECs (Gaiger et al, 2015; Kawano, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Morais et al (2017) show that women are the driving force in SEOs like SECs. By contrast, Wamba et al (2018) show that the presence of women has a negative effect on the social and financial performance of these organizations. This fuzziness is troubling, considered that gender equality is endemic to the very concept of SECs (Gaiger et al, 2015; Kawano, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Gender does not play a role in this configuration, but democracy and specialization appear as conditions that complement formalization and member selection policies . Specialization may amplify efficiency by organizing working groups that support specific activities and operationalize processes and plans (Pansera & Rizzi, 2020; Wamba, Bengono, Sahut, & Teulon, 2018). The role of democracy is widely acknowledged in SECs and SEOs (Defourny & Nyssens, 2017; Gordon, 2015) because it allows active participation in decision‐making and goal setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our endeavour found that around 16 of the 42 reviewed articles with theories applied the agency theoretical lens only and related it to different sets of CG actors. Grounded on agency theoretical underpinning, studies mainly looked into the conflicting interests of two diverse groups, commonly known as principals (owners) and agents (managers) (Hartarska, 2005; Kyereboah-Coleman and Osei, 2008; Tchakoute-Tchuigoua, 2010; Thrikawala et al , 2016a; Wamba et al , 2018) to mention a few. These studies, motivated by agency theory framing, have provided us with a rich insight into board monitoring and control of MFI managers (agents).…”
Section: Reporting and Dissemination Of Findingsmentioning
confidence: 99%
“…However, empirical evidence of this relationship is incongruent. For instance, some studies found that governance structure positively influences the performance of MFIs (Allemand et al , 2013; Augustine, 2012; Augustine et al , 2016; Chakrabarty and Bass, 2014; Dato et al , 2018; Kyereboah-Coleman and Osei, 2008; Mori et al , 2015; Nihel and Younes, 2015; Pascal et al , 2017; Strøm et al , 2014; Tchakoute-Tchuigoua, 2010; Thrikawala et al , 2016a, 2017; Wamba et al , 2018) to mention few. Other studies found that governance structure both positively and negatively affects MFI performance (Abate et al , 2014; Bakker et al , 2014; Bassem, 2009; Van Damme et al , 2016; Estapé-Dubreuil and Torreguitart-Mirada, 2015; Gohar and Batool, 2015; Hartarska, 2005; Hartarska and Mersland, 2012; Mersland and Strøm, 2009).…”
Section: Reporting and Dissemination Of Findingsmentioning
confidence: 99%